Understanding and Practice of Religious Tolerance: A Study of the Living Qur’an in Madura, Indonesia - Takdir, Mohammad; Sumbulah, Umi (Universitas Islam Negeri Mataram, 2024)
This study intends to investigate how Muslims understand and practice religious tolerance teachings with other religious communities in Madura, Indonesia. The knowledge and forms of tolerance practices in the dynamics of the lives of people of different religions in Pamekasan, Madura, are described in this study using a qualitative-descriptive research approach. This research uses observation, interviews, and documentation to examine empirical data in the field. According to field observations and interviews, the findings of this study led to three significant conclusions. First, Pamekasan people understand that religious tolerance is essential for establishing a peaceful life with other religious communities. In other words, society has practiced the teachings of tolerance according to what is understood in the verses of the Qur’an about the importance of coexistence with different religious communities. Second, the concrete form of the practice of the values ​​of tolerance is embodied in socio-religious life, such as social service activities, ritual traditions, and helping each other celebrate religious days. Third, the factors forming the values ​​of tolerance contained in the verses of the Qur’an are the harmony of the four houses of worship in one complex, local wisdom, and the role of interfaith organizations.